High‐Throughput Nanofabrication of Metasurfaces with Polarization‐Dependent Response. Issue 20 (26th July 2020) - Matricardi, Cristiano; Garcia‐Pomar, Juan Luis; Molet, Pau; Pérez, Luis Alberto; Alonso, Maria Isabel; Campoy‐Quiles, Mariano; Mihi, Agustín
Abstract: Metal nanostructures offer exciting ways to manage light at the nanoscale exploited in fields such as imaging, sensing, energy conversion, and information processing. The optical response of the metallic architectures can be engineered to exhibit photonic properties that span from plasmon resonances to more complex phenomena such as negative refractive index, optical chirality, artificial magnetism, and more. However, the latter optical properties are only observed in intricate architectures, which are highly demanding in terms of nanofabrication and hence less scalable and far away from device implementation. Here, a series of metasurfaces covering centimeter areas and operating in the visible spectrum are presented, which are produced from the combination of nanoimprinting lithography and oblique angle metal evaporation. The potential of this scalable approach is illustrated by easily fabricating metasurfaces engineered to exhibit artificial optical magnetism, tunable linear polarization dependent response, chirality with g ‐factor of 0.2, and photoluminescence enhancement of 20 times over a 9 mm 2 area. Abstract : A combination of nanoimprinting lithography and oblique angle metallization is used to produce metasurfaces composed of unit cells with different degrees of asymmetry. This scalable and straightforward technique results in 2D arrays with linear polarization dependent response, chirality, optical magnetism, or strong near‐field enhancement over large areas.